2017
DOI: 10.4172/2327-5073.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids for Amoxicillin and Ciprofloxacin Resistance in Escherichia coli Isolate Causing Urinary Tract Infection

Abstract: Background: Escherichia coli causes urinary tract infection (UTI), one of the most frequent bacterial infections in humans, shows resistance to various commonly prescribed antibiotics. This is termed as multi drug resistance, which is increasing among E. coli. The multi-drug resistant E. coli isolates harbor multiple plasmids that might be responsible for antibiotic resistance. The resistance can be transferred among bacteria through horizontal transfer of the genetic materials. Objectives: We undertook this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The only isolate in the present investigation with 100% resistance against the tested antibiotics (EC91) was seen to carry multiple bands with different sizes and this could be the contributory factor in the exhibited resistance in this isolate. Also studies have shown that penicillin resistant E. coli harboured plasmids that are within the range of 30 kb and above [33], such as is the case of the E. coli isolates in the present investigation. Thus, E. coli showing MDR have been reported to carry multiple plasmids of different sizes and this has been the case of those encountered in this study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The only isolate in the present investigation with 100% resistance against the tested antibiotics (EC91) was seen to carry multiple bands with different sizes and this could be the contributory factor in the exhibited resistance in this isolate. Also studies have shown that penicillin resistant E. coli harboured plasmids that are within the range of 30 kb and above [33], such as is the case of the E. coli isolates in the present investigation. Thus, E. coli showing MDR have been reported to carry multiple plasmids of different sizes and this has been the case of those encountered in this study.…”
Section: Discussionsupporting
confidence: 66%
“…With high resistance being attributed to plasmids having molecular weights of 23-26 kb, the resultant high resistance as seen in this study could be due to the 30kb and above of the molecular weight of the plasmids as well as the presence of multiple sizes amongst the isolates. However, it is known that E. coli isolates carry multiple plasmids which could be the reason why they are resistant to antibiotics [33]. The only isolate in the present investigation with 100% resistance against the tested antibiotics (EC91) was seen to carry multiple bands with different sizes and this could be the contributory factor in the exhibited resistance in this isolate.…”
Section: Discussionmentioning
confidence: 56%
“…About 90% of the E. coli isolates causing UTI in the North-East region of Bangladesh were reported as MDR, and the multidrug resistance in E. coli might be either plasmid or chromosomal DNA mediated or the both. 2,13 In this study, the efflux pump system has been discussed as one of the reasons for multidrug resistance in the MDR E. coli isolates causing UTIs and omeprazole may be an efflux pump inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Susceptible bacteria can acquire resistance to an antimicrobial agent through mutation, degradation, or changing the structure of antibiotic, efflux pump, and conjugation and/or transformation of the plasmid. 2,13,14 Efflux pump proteins, found in both Gram-positive and Gram-negative bacteria as well as in eukaryotic microorganisms, 15 are transporter proteins involved in the extrusion of toxic substrates from within cells into the external environment. The impact of efflux mechanisms on AMR is large, and antibiotics can act as inducers and repressors of the expression of some efflux pump proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of three heavy molecular weight plasmids found in E. coli corroborates previous study which showed that E. coli isolates carry multiple plasmids which could be the reason for their resistant to antibiotics [21]. Bacteria antibiotics resistance patterns are sometimes associated with the presence of large plasmids and ability of plasmids for conjugation process [22].…”
Section: Discussionmentioning
confidence: 99%